Potential candidates from a functional food Zanthoxyli Pericarpium (Sichuan pepper) for the management of hyperuricemia: high-through virtual screening, network pharmacology and dynamics simulations - Chen, Meilin; Chen, Xiaomei; Chen, Qinghong; Chu, Chenyang; Yang, Shuxuan; Wu, Chuanghai; You, Yanting; Hung, Andrew; Yang, Angela Wei Hong; Sun, Xiaomin; Zhou, Lin; Zhao, Xiaoshan; et al. (Frontiers in Endocrinology, 2024)
Introduction: Hyperuricemia (HUA) is a metabolic syndrome caused by purine metabolism disorders. Zanthoxyli Pericarpium (ZP) is a medicinal and food homologous plant, and its ripe peel is used to treat diseases and as a spice for cooking. Some studies have shown that ZP can inhibit the formation of xanthine oxidase and reduce the production of uric acid.Methods: Through network pharmacology, ZP's potential targets and mechanisms for HUA treatment were identified. Databases like TCMSP, UniProt, and Swiss Target Prediction were utilized for ZP's active ingredients and targets. HUA-related targets were filtered using GeneCards, Drugbank, and Open Targets. Core targets for ZP's HUA treatment were mapped in a PPI network and analyzed with Cytoscape. GO and KEGG pathway enrichments were conducted on intersected targets via DAVID. Molecular docking and virtual screening were performed to find optimal binding pockets, and ADMET screening assessed compound safety. Molecular dynamics simulations confirmed compound stability in binding sites.We identified 81 ZP active ingredient targets, 140 HUA-related targets, and 6 drug targets, with xanthine dehydrogenase (XDH) as the top core target. Molecular docking revealed ZP's active ingredients had strong binding to XDH. Virtual screening via Portein plus identified 48 compounds near the optimal binding pocket, with 2'-methylacetophenone, ledol, beta-sitosterol, and ethyl geranate as the most promising. Molecular dynamics simulations confirmed binding stability, suggesting ZP's potential in HUA prevention and the need for further experimental validation.Our study provides foundations for exploring the mechanism of the lowering of uric acid by ZP and developing new products of ZP. The role of ZP in the diet may provide a new dietary strategy for the prevention of HUA, and more experimental studies are needed to confirm our results in the future.